Peran Harga dan Kualitas Produk Bagi Konsumen Melakukan Pembelian Ulang di Toko Roti Primadona Surabaya - Mochamad Irfan (Forum Kerjasama Pendidikan Tinggi, 2022)
The efforts of bakers to compete in the bakery industry are shown by always paying attention to competitors' prices and developing quality products for customers. Bakers strives to achieve customer satisfaction. Customer satisfaction and a pleasant experience provide a greater opportunity to make a decision to repurchase bakery products. repurchase decisions also reflect the price and quality of products that meet customer expectations. The purpose of this study was to determine the effect of price and product quality on repurchase decisions at Primadona Surabaya bakery. This type of research is explanatory research at the Primadona bakery, Surabaya. The population in this study were all customers who had bought bread and cakes at Primadona Surabaya bakery with 100 respondents. The results showed that the price had a significant effect on the repurchase decision. In addition, purchasing decisions made by consumers are also significantly influenced by product quality. Price and product quality have been shown to have a significant influence on the formation of joint repurchase decisions